Developing a databank for multiple transfusion patients: Rh antigen and phenotype distribution among 3000 regular blood donors in Iran. (June 2021) - Bakhshandeh, Zahra; Amirizadeh, Naser; Maghsoodlu, Mahtab; Oodi, Arezoo; Naghi, Amirali; Khazaeli, Ali Arab; Azarkeivan, Azita
Highlights: Alloimmunization is an important complication of persistent blood transfusions in multiple transfusion patients. Alloantibodies against the Rh antigens are frequently detected in thalassemia patients. Extensive matching for the five most common Rh antigens likely reduces the risk of alloimmunization. Abstract: Background: Rhesus (Rh) blood group system is clinically the most significant protein-based grouping system. The Rh system is of vital importance in blood transfusion, and incompatibility between the donor and recipient leads to alloimmunization. Alloimmunization is commonly seen in multiple-transfusion recipients (e.g. thalassemia patients). There are a few studies about the prevalence of Rh antigens, except for D, in Iran; and regarding the high prevalence of thalassemia in the country, in this study we have determined antigens and phenotypes of the Rh among population of regular blood donors with the aim of developing a detailed Rh databank. Materials and methods: This cross-sectional study randomly enrolled 3000 regular blood donors from three provinces of Sistan-Balouchestan, Khuzestan and Gilan in Iran, from September 2018 to May 2019. A fully automated system, based on hemagglutination, was used to Rh typing of blood samples. Results: The prevalence of Rh antigens were as follows: D: 88.9 %; E: 30.9 %; C: 74.1 %; e: 96.2 %; and c: 72.8 %. The most common antigen and phenotype were "e" and R1 r (DCcee), respectively. Conclusion: Due to the high rate of alloimmunization incidence against Rh blood group antigens among multiple transfusion recipients, development of regular blood donor's Rh databank can facilitate extensive matching for the Rh antigens and it likely reduces the risk of alloimmunization.